Dr. Edwin Wright Letters: Emma Miller - (Author); (Interviewer); (Publisher) (1961)
Notes - Ms. Emma Miller discusses her family's travels and early life in Athabasca. She talks of her parent's first jobs (working at Mr. Ike Gagnon's mill) and of living on rabbits and beans in the winter as ""money for meat was scarce. Ms. Miller talks of helping put shingles on Parkhurst school and of being married there to Mr. Peter Miller. Ms. Miller talks of the need and difficulty in recruiting physicians to the far North and how the town finally landed Doctor Meyer (each family agreed to pay twelve dollars per year to the doctor) (2 pages)